Rectal metastasis from Breast cancer: A rare entity. (2015) - Ng, Cho Ee; Wright, Lucie; Pieri, Andrew; Belhasan, Anas; Fasih, Tarannum
Highlights: In patients with history of Invasive lobular cancer of breast with positive faecal occult blood with or without bowel symptoms should have high clinical suspicion of bowel metastasis. Breast cancer is the second most common cancer to metastasise to anywhere along the gastrointestinal tract from oropharynx to anus. Abstract: Introduction: Breast cancer metastases occurs in around 50% of all presentation. It is the second most common type of cancer to metastasise to the GI tract but this only occurs in less than 1% of cases. Presentation of case: We report a case that underwent treatment for invasive lobular cancer (ILC) of the breast and 5 years later was found to have rectal and peritoneal metastasis. She is currently receiving palliative management including chemotherapy in the form of weekly Paclitaxel (Taxol ® ) and stenting to relieve obstruction. Conclusion: There should be high clinical suspicion of bowel metastasis in patients presenting with positive faecal occult blood with or without bowel symptoms even if the incidence is less <1% of metastases, particularly in cases where the initial breast tumour was large, with positive axillary nodes.